Avaliação comportamental, de mecanismos antidepressivos e alterações metabólicas da combinação de mirtazapina e ácido lipóico em modelo de depressão induzido por corticosterona - Oliveira, Tatiana de Queiroz (2019)
Depression is a disease characterized by depressed mood, cognitive deficits, sleep and appetite disorders that affects about 320 million people in the world and is the leading cause of disability. The model of depression induced by corticosterone alters the hypothalamic-pituitary-adrenal axis producing symptoms like depression. The present work sought to elucidate the neurochemical effects and mechanisms involved in the association of mirtazapine (MIRT), an antidepressant used in the treatment of resistant depression, but with important side effects such as sedation and weight gain, with lipoic acid (ALA) anti-inflammatory and antioxidant actions. Adult male mice received 0.3% Tween 80, corticosterone (CORT 20 mg / kg) MIRT (3 mg / kg), ALA (100 or 200 mg / kg), alone or associated for 21 days. On the last day of treatment, the animals were subjected to the following tests: tail suspension, forced swimming, Splash test, sucrose preference, object recognition and Y Maze Spontaneous Alternation. In addition, we analyzed the concentrations of: total cholesterol and fractions, corticosterone; changes in the weight of animals; expression of IL-6 and IL-4 cytokines; and protein expression and activation of Akt (total and phosphorylated), serotonin and synaptophysin transporter and activation of caspase 3 in HC were also addressed. The present study demonstrated that chronic corticosterone administration promoted changes in depressive-like behavior, memory deficit, metabolic changes (total cholesterol and LDL), changes in corticosterone and interleukin levels in the HC of mice (increase of IL6 and reduction of IL4), as well as increase of SERT in this cerebral area. Treatment with ALA200 + M reversed the depressive and cognitive symptoms evaluated, as well as reduced the level of corticosterone in the animals and the expression of SERT, although the association did not show synergism; and ALA100 + M reversed the weight gain caused by MIRT treatment. This provides evidence that the combination of ALA + MIRT may be a perspective of treating depression, however, further research should be conducted for this purpose.